TEM characterization of III-V diode structure grown on GeOI structures - Myat Kyawt Ei. (2012)
A highly sensitive semiconductor device, avalanche photo diode, exploits photoelectric effect to convert light to electricity. APDs which can act like photo detectors provide a built-in first stage gain through avalanche multiplication. When the photo generated carriers acquire enough energy from the electric field to impact ionize, internal current gain can be achieved in avalanche photodiodes. [1]Therefore, by using APD instead of a pin diode or converting the weak optical signal into an electrical current, the internal gain mechanism can improve the signal-to-noise ratio (SNR) of an optical receiver. However, the avalanche process is stochastic in nature and increased sensitivity is limited by the level of excess noise generated by avalanche process. This